Deixis Analysis on the Pink Sweat$ Song’s Lyric - Wiya Suktiningsih; Ahmad Yardi; M.Zaki Pahrul Hadi; Ni Nyoman Widani (Humanitatis : Journal of Language and Literature, 2022)
A song can be said as a form of expression of the songwriter, about the life experiences he has gone through. Pink Sweat$ is an American singer and songwriter with the R&B genre of music. Pink Sweat$ made its record debut in the music world in 2018 to date. The song Honesty was released in 2018 and received a certificate platinum from the RIAA. In 2020, songs 17 and At My Worst get more than 100 million fans who downloaded the song on the spotify US digital platform. The song from Pink Sweat$ as the object of research, how the simplicity of the lyrics contains many meanings and able to attract music fans to listen to it. To reveal this, the researcher uses the deixis theory of George Yule (1996) in a pragmatic study. Researchers used a qualitative research method approach in this study. The results showed that the use of personal deixis was used more in the three songs, compared to temporal deixis and spatial deixis. Deixis persona refers to Pink Sweat$ himself, it can be said that this song is his personal love life experience.